Exploring the urban park use, preference and behaviours among the residents of Kuala Lumpur, Malaysia - Maruthaveeran, Sreetheran (Elsevier, 2017)
The understanding of cross-cultural upon park usage is vital to be enhanced among public since findings that been discovered in the Western context are not own any similarities with the Asian context. In fact, it has been in a long run for the Western nations to primarily contextualized and conceptualized much on the literature of park usage. This study aims to look at how the people use and perceive urban parks in their daily life in the Malaysian cultural context, and also highlights the constraints faced by Malaysians while using the urban parks in the city of Kuala Lumpur. A survey consisted of 669 urban park users as the sample of the study (365 men, 304 females) aged between 18 and 73 years (M = 34.85, SD = 11.46) were conducted in five urban parks in Kuala Lumpur. Respondents were recruited based on a random sampling method, which composed of three main ethnic groups in Malaysia. Malaysians wanted to use the urban parks for multiple purposes including active activities and others. Most of them would visit the parks and spend their time in a group consisting of family members or friends rather than alone. The percentage of respondent with 74.7% stated their reason of visiting the urban park in order “to get fresh air”, followed by the factor of reducing stress and relaxing with 69.7%; and the latter reason would be “to exercise, play games or keep in shape” with 61.4%. More than 80% of the respondents claimed the parks in Kuala Lumpur are safe to be visited. This is because, majority of the respondents tend to visit the parks in group of family or friends rather than alone. In addition, most of the respondents would run their activities in parks during the weekends, which simultaneously make them to enjoy their day in such comfortable and secure way. The findings of this survey would contribute to a better understanding of the present park usage of Kuala Lumpur residents. With a better understanding of current park-visiting habits, various constraints faced by the residents related to public security and safety, the Kuala Lumpur City Hall have been suggested to develop more comprehensive strategy in order to provide engagement and urban parks stimulation for its residents. In addition, this study is also fruitful for Kuala Lumpur future parks in terms of its development, design and management.